1961
DOI: 10.1111/j.1365-2621.1961.tb00799.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition of Meat Tissue Lipids

Abstract: The lipids extracted from beef and pork muscle were fractionated into triglycerides, cephalins, and a mixture of lecithins and sphingomyelins. The fatty acid composition of these fractions was determined, and the possible effect of phospolipids on meat flavor was evaluated.Cold-water extracts of lean beef and lean pork contain desirable meat-flavor precursors. These extracts do not, however, contain any appreciable proportion of the lipids present in the lean meat. Lipids, particularly the phospholipids, are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
1
1

Year Published

1964
1964
1993
1993

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(50 citation statements)
references
References 5 publications
7
41
1
1
Order By: Relevance
“…The respective levels of oleic acid for the liver, heart, kidney, LD and BF muscles indicated that the skeletal muscles contained more than 1.5 times, in some instances nearly double, that in liver, heart and kidney. This agreed with previous studies with other species (Hornstein et al, 1961;Duncan and Garton, 1967;Eichhom et al, 1986;Sinclair and O'Dea, 1987). Analyses of triglycerides derived from various tissues of pig, horse, steer and sheep have shown that those of internal body tissues contained much higher proportion of saturated fatty acids than those of external or sub-cutaneous tissues (Hilditch and Williams, 1964;Eichhorn et al, 1986;Devendra, 1988).…”
Section: Resultssupporting
confidence: 94%
“…The respective levels of oleic acid for the liver, heart, kidney, LD and BF muscles indicated that the skeletal muscles contained more than 1.5 times, in some instances nearly double, that in liver, heart and kidney. This agreed with previous studies with other species (Hornstein et al, 1961;Duncan and Garton, 1967;Eichhom et al, 1986;Sinclair and O'Dea, 1987). Analyses of triglycerides derived from various tissues of pig, horse, steer and sheep have shown that those of internal body tissues contained much higher proportion of saturated fatty acids than those of external or sub-cutaneous tissues (Hilditch and Williams, 1964;Eichhorn et al, 1986;Devendra, 1988).…”
Section: Resultssupporting
confidence: 94%
“…The variation, although small, shows that phosphatidylethanola mine tends to be present in greater quantities in the tis sues with less total lipid content while the sphingomyelin is relatively somewhat more abundant in the tissues with greater total lipid content. The lecithin content agrees quite well with the values reported by Hornstein et al (1961) for aged pork muscle, but the cephalin content found in this study is substantially lower than reported.…”
Section: Review Of Literaturesupporting
confidence: 78%
“…The fatty acid distribution in beef tongue lipid approximated that foulid in beef and pork muscle tissue (Hornstein et al, 1961 ;Slover et al, 1964). The total polyunsaturated fatty acid content was relatively low, the fatty acids consisting of 5-6s linoleic plus arachidonic acids.…”
Section: Results and Ikxjssionmentioning
confidence: 94%